2016
DOI: 10.5194/bg-2016-459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Size-dependent response of foraminiferal calcification to seawater carbonate chemistry

Abstract: The response of the marine carbon cycle to changes in atmospheric CO 2 concentrations will be determined, in part, by the relative response of calcifying and non-calcifying organisms to global change. Planktonic foraminifera are responsible for a quarter or more of global carbonate production, therefore understanding the sensitivity of calcification in these organisms to environmental change is critical. Despite this, there remains little consensus as to whether, or to what extent, chemical and 5 physical fact… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…In both modern and geological field studies of a variety of species, multiple drivers of weight change are indicated. In general, calcification is energetically more difficult outside optimum CO 2 conditions for each species (de Nooijer et al, ; Foster et al, ; Henehan et al, ) and at lower carbonate ion concentrations (Kroeker et al, ). In laboratory experiments, a clear reduction of weight in response to lower carbonate ion changes is documented (Beer et al, ; Bijma et al, ; Bijma et al, ; Henehan et al, ; Lombard et al, ; Russel et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both modern and geological field studies of a variety of species, multiple drivers of weight change are indicated. In general, calcification is energetically more difficult outside optimum CO 2 conditions for each species (de Nooijer et al, ; Foster et al, ; Henehan et al, ) and at lower carbonate ion concentrations (Kroeker et al, ). In laboratory experiments, a clear reduction of weight in response to lower carbonate ion changes is documented (Beer et al, ; Bijma et al, ; Bijma et al, ; Henehan et al, ; Lombard et al, ; Russel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Marine calcifying organisms play a fundamental role in the inorganic carbon cycle (Boyce et al, ; Henehan et al, ). Carbonate production in the ocean is roughly equally divided between the shelf and the open ocean (Cartapanis et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in ocean chemistry also may have affected morozovellid calcification and explain to some extent the observed test size reduction. Recent culturing and open ocean observations suggest that acidification can affect variably sized foraminifera differently, such that larger planktic foraminifera preferentially reduce their calcification (Henehan et al, ). We cannot exclude that morozovellids may have decreased their maximum size as a consequence of a drop in pH, because there are several short‐term negative CIEs within the EECO probably signifying addition of CO 2 to the ocean and atmosphere (e.g., Dickens et al, ; Zeebe et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The highly significant relationship between size and weight also shows that factors such as secondary precipitation, dissolution, or sediment infilling were minimal or consistent through time. However, scatter within this relationship does demonstrate variability in the size and weight relationship for any given individual foraminifera, such as the influence of body size on response to carbonate chemistry (Henehan et al, ) or the influence of temperature and nutrients during an individual's lifetime. Moreover, no significant relationship was found between sample average area density and average area ( p value = 0.24), indicating that size normalization of weights was effective in limiting bias due to size change.…”
Section: Resultsmentioning
confidence: 99%